STUNTING AND ITS ASSOCIATED FACTORS IN SCHOOL-AGE CHILDREN OF WAH CANTONMENT, PAKISTAN. : J Peop Univ Med Health Sci. 2025:15(3), 36-43. http://doi.org/10.46536/jpumhs/2025/15.03.656 - Sohail Ashraf1, Saleh Ahmed2, Saba Mushtaq3, Muhammad Ahmad Mughal4, Khola Waheed Khan5, Rabia Rehman6, (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2025)
BACKGROUND: Stunting is used as one of the indicators of malnutrition in children. Children are considered stunted if their height-for-age is less than two standard deviations of the World Health Organization (WHO) Child Growth Standards median. Data related to stunting in older children is scanty so this study was planned. OBJECTIVE: To determine the frequency of stunting in school- going children of Wah Cantonment and its association with their gender and type of school. METHODOLOGY: The study was conducted using a cross-sectional design among primary and middle schools in Wah Cantonment, Pakistan, belonging to both the public and private sectors from August 2024 to October 2024, using a convenient sampling technique. Data was collected using a structured questionnaire and was analysed using SPSS version 25. RESULTS: 11.6% of the children were found to be stunted. Out of 60 children with stunting, 27 were males and 33 were females (p- value=0.27). 61.7% of these stunted children were found to be enrolled in public sector schools (p- value=0.02). CONCLUSION: The frequency of stunting was relatively lower than in other regions of Pakistan. There was no difference in stunting across genders. The majority of the children with stunting were enrolled in public sector schools, highlighting the need for targeted interventions in public schools to reduce stunting.